Ảnh hưởng của văn hóa chấp nhận rủi ro đến hiệu quả huy động vốn khởi nghiệp của Gen Z tại Việt Nam: Vai trò trung gian của tín hiệu gọi vốn và điều tiết của thể chế và hạ tầng hỗ trợ - Nguyễn Thị Mỹ , Dung; Lương Minh , Đức; Trần Đình , Lộc (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2026)
This study examines the effect of risk-acceptance culture on startup fundraising effectiveness among Gen Z in Vietnam, while considering the mediating role of fundraising signals and the moderating role of institutional and support infrastructure conditions. Survey data collected from Gen Z individuals serving as founders, co-founders, or core team members in startups were analyzed using measurement scale validation and structural equation modeling techniques. The findings show that financial literacy, risk orientation, and risk-acceptance culture at both community and individual levels contribute positively to fundraising signals. Fundraising signals, in turn, have a positive effect on fundraising effectiveness, and this effect becomes more evident when institutional and support infrastructure conditions are favorable. The study suggests that enhancing financial literacy, standardizing fundraising materials, and improving ecosystem support conditions can help Gen Z startups improve their access to capital